A Few Remarks on the British Empire – Past and Present (The British Empire: Interdisciplinary Deliberations, 2019)
This collection of papers is devoted to the various aspects of British Empire, its origins, existence and legacy. An interdisciplinary character of the studies is reflected in a variety of contexts and perspectives informed by discourses on culture, international relations, and politics. Issues such as the emergence and carrying out of the imperial policy, importance of propaganda, a unique shape and character of the British Empire, as well as an in-depth discussion regarding its legal and political justification play a prominent role. At the same time, much to our regret, a plethora of other, equally important fields, linguistics and cultural studies in particular, are either underrepresented or excluded for reasons beyond our control. Of special interest are gender issues studied from different angles, including the beginnings of women’s travel narratives that originated in Great Britain. Related to this are the accounts written by British travelers in Poland under the Russian partition, a subject of paramount importance in light of the centennial anniversary of the restoration of Poland’s sovereignty. In a similar vein, British presence in the territories of Poland under partitions is the focus of one of the essays. Another field of study are legal and political facets of the British Empire and its aftermath. Here, too, one can observe a great diversity in the treatment of topics and choice of approaches: from the rather obscure legal body known as the Judicial Committee of the Privy Council, the perception of which as anachronistic is however strongly contested, to the wider issues connected with the imperial policy, or the relation between British socialism and the Empire present in the aesthetic rather than political postulates of the Victorian sages. Criticism of British colonial legacy is well-known in the academia and regular publications. It could not be overlooked in this collection, either. Post-colonialism is explored in two papers approaching it from a literary perspective. Nevertheless, the actuality and continuity of imperial heritage that surfaces in almost every dimension of the contemporary world – from ethics and morality, through logic and the methods of reasoning, to the current formulations of the universal human rights as expressed and warranted by the UNO and state constitutions, proves that the sun has never set on the British Empire. The most tangible evidence to support that claim is the Commonwealth of Nations, an association of otherwise sovereign states that in virtually every corner of the world keep British lineage alive.